Juridical Analysis of Cancellation of Bonding Agreements of Selling & Buying a Plan of Land - Taufik Rakhman; Ahmad Khisni; Amin Purnawan (Sultan Agung Notary Law Review, 2021)
The purpose of this study was to determine and analyze the process of canceling the binding sale and purchase agreement for a plot of land. To find out and analyze the legal consequences of the cancellation of the binding sale and purchase agreement for a plot of land in the construction of legal certainty.The method used by the researcher is Juridical Empirical (sociolegal research)and The specifications in this study are descriptive analytical. Based on the results of the study that The process of canceling the binding sale and purchase agreement for a plot of land is made by the parties to make their own cancellation deed in carrying out any legal actions, all possibilities can occur, including if the parties have agreed to cancel the previously agreed sale and purchase agreement, through a court order to cancel the agreement that is not Legal consequences can only be carried out by a judge or higher institution or competent institution, automatically canceling the agreement, then the contents of the agreement are automatically null and void by law and even considered that the agreement never existed or never occurred. Legal consequences Against the cancellation of the binding agreement on the sale and purchase of a plot of land in construction, legal certainty, namely:null and void by law, namely the non-fulfillment of objective conditions (Article 1320 of the Civil Code): a certain matter, a permissible/halal/legal cause, the agreement cannot be executed, because the agreement is not simply canceled, but cannot be implemented or forwarded to the next process, because it is still have a certain legal status.